Political Transformation and the Transition of Islamic Civilization from the Classical to the Modern Era, and Islam’s Contribution to World Knowledge - Mardhatillah, Mardhatillah; Samad, Duski; Firdaus, Firdaus (The Future of Education Journal, 2025)
This paper examines the transformation of Islamic politics and civilization from the classical period to the modern era, as well as the contributions of Islam to the development of global knowledge. In the classical period, Islamic civilization was characterized by strong political institutions, intellectual openness, and the integration of religious and rational sciences, which enabled significant advancements in science, medicine, philosophy, and social thought. However, internal political fragmentation, external pressures, and colonial domination led to the decline of Islamic political power and intellectual influence. The modern period marks a phase of transformation in which Muslim societies faced the challenges of modernization, Western influence, and the reconfiguration of political and intellectual frameworks. Despite these challenges, Islam continued to contribute to global knowledge through its rich scientific heritage, methodological approaches, and ethical perspectives. The transmission of Islamic knowledge to Europe played a crucial role in shaping modern science and the Renaissance. This study highlights that the transformation from classical to modern Islamic civilization reflects both continuity and change, demonstrating the enduring relevance of Islamic intellectual traditions in the contemporary world.